Os adolescentes portugueses e a igualdade de oportunidades dos migrantes - Guedes, Fábio Botelho (2019)
Understanding the equal opportunities of immigrants as one of the fundamental humanity rights, migrant populations have been especially prominent, being present in various social and political discussions. The objective of the study was to analyse the characteristics of adolescents who express a more positive attitude towards cultural diversity. A total of 5695 Portuguese adolescents (46.1% boys) participated in the study, from the 8th, 10th and 12th grades, in Portugal. The sample was collected as part of the Health Behaviour in School aged Children (HBSC) study. Gender differences have been identified, being females and adolescents who meet non-Portuguese youth who have a more positive connection with equal opportunities for immigrants. Age and curiosity about meeting people from other places also have an explanatory value of equal opportunities. The variables related to cultural diversity and well-being help to better explain the perception of the equality of opportunities of migrants in the eyes of Portuguese adolescents, however it is the youngest and the women who present a more positive perception. Development of actions to encourage the valorisation of diversity and the promotion of common activities is necessary, emphasizing the promotion of other personal and/or social-emotional competences in promoting well-being and social cohesion.